2012
DOI: 10.1074/jbc.m111.333484
|View full text |Cite
|
Sign up to set email alerts
|

Two-step Mechanism for Modifier of Transcription 1 (Mot1) Enzyme-catalyzed Displacement of TATA-binding Protein (TBP) from DNA

Abstract: Background: Mot1 catalyzes ATP-dependent disruption of TBP-DNA complexes. Results: Mot1 binding to TBP-DNA complexes induces a conformational intermediate in which DNA is unbent. Conclusion: We propose a two-step mechanism for Mot1 in which DNA unbending is followed by ATP-dependent DNA translocation. Significance: Mot1 is a model Snf2/Swi2 enzyme whose catalytic mechanism is relevant for understanding how other enzymes in the family function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…We suggest that the non-equivalent roles of DNA bases at the same position along the DNA length but on opposite strands argue for strand specificity in Mot1 action. Prior work provided evidence for Mot1-induced DNA unbending (14,40), which was suggested to "prime" the TBP-DNA complex for dissociation (Fig. 7).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We suggest that the non-equivalent roles of DNA bases at the same position along the DNA length but on opposite strands argue for strand specificity in Mot1 action. Prior work provided evidence for Mot1-induced DNA unbending (14,40), which was suggested to "prime" the TBP-DNA complex for dissociation (Fig. 7).…”
Section: Discussionmentioning
confidence: 94%
“…Probe-specific Difference in ATPase Conformation-To determine whether DNA sequence can influence ATPase conformation, we tested a DNA probe called Moyle6Fe, which was used previously (40) and contains the same TATA sequence as probe 6Fe, but the upstream DNA sequence is different. We also compared the effect of ADP-AlF 4 with ADP-BeF 3 , a "ground state" ATP analog (41,42), using each of these two DNA probes.…”
Section: Resultsmentioning
confidence: 99%
“…The Swi2/Snf2 ATPase domain of Mot1 contacts DNA ϳ17 bp upstream of TBP and translocates toward TBP, loosening its association of TBP with DNA. Last, the latch of Mot1 occupies the DNAbinding groove of TBP, displacing the Mot1-TBP complex from DNA and preventing TBP from rebinding DNA (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…As previously shown by the crystal structure of TBP-DNA, TBP bends the promoter DNA approximately 90° (Kim et al 1993). When Mot1 binds to TBP-DNA the FRET study showed that Mot1 straightened the bent DNA somewhat, potentially priming the TBP for dissociation (Moyle-Heyrman et al 2012). Importantly, this unbending of the DNA is in the absence of ATP.…”
Section: The Role Of Mot1 In Transcriptional Regulationsupporting
confidence: 55%
“…Importantly, this unbending of the DNA is in the absence of ATP. A model was proposed that after the unbending of DNA that Mot1 then went through multiple rounds of ATP hydrolysis to remove TBP from DNA (Sprouse et al 2008b, Moyle-Heyrman et al 2012). The current model of Mot1-mediated removal of TBP from DNA is illustrated in a simple cartoon in Figure 1.5.…”
Section: The Role Of Mot1 In Transcriptional Regulationmentioning
confidence: 99%